PEMANFAATAN ARTIFICIAL INTELLIGENCE CHATGPT DALAM MENINGKATKAN KREATIVITAS SISWA DI SMK PERTIWI KUNINGAN - Galuh Dwi Andika; Yoyo Zakaria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of Artificial Intelligence (AI), particularly ChatGPT, has opened new opportunities to support the learning process and to foster students' creativity. This study aimed to analyze differences in students' creativity in using ChatGPT between students who participated in an AI Course and those who did not at SMK Pertiwi Kuningan, to determine the appropriateness of ChatGPT responses based on students' prompts, and to describe students' responses toward the use of ChatGPT in enhancing creativity. A quantitative approach was employed using a Quasi Experimental method with a Posttest-only Nonequivalent Group Comparison design. The sample consisted of 40 students divided into an AI Course group and a Non-AI Course group. Data were collected through a performance test assessed with a creativity rubric and a questionnaire, both validated through expert judgment, with empirical validity and reliability tested using SPSS on 40 respondents outside the main sample. All questionnaire items were valid (r-count > r-table 0.312) with a Cronbach's Alpha of 0.718. The AI Course group achieved a mean posttest score of 30.00, while the Non-AI Course group obtained 13.20. The Independent Samples t-Test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference in creativity between the two groups. Both groups responded positively toward ChatGPT use; however, students who had learned prompt engineering produced more relevant ChatGPT responses and demonstrated higher creativity.